Fabrication of metallic pressure vessels - Greulich, Owen R.; Jawad, Maan H. (Wiley-ASME Press series., 2022)
"Much of the equipment used in the refining and processing industries is known as Process Equipment. Most pieces of process equipment are designed to perform specific, singular tasks. Process equipment can be used for tasks a varied as storage, controlling flow, and containing chemical reactions. Fabrication involves making products and components from raw or semi-finished materials by cutting, shaping and joining sections of metal together. Fabrication processes include cutting, folding, machining, shearing, stamping and welding"--